The Influence Of Leadership Ethics And Organizational Culture - Sudrajat, Yayat; Komariyah, Imas; Sekartadjie, Gilang (Program Pascasarjana STIE Amkop Makassar, 2023)
This study set out to determine how organizational performance is impacted by commitment, organizational culture, and ethical leadership. As a mediator in the relationship between ethical leadership and organizational performance, commitment is also examined, as is the link between organizational culture and performance. Primary data for this study is gathered through distributing questionnaires. A quantitative research strategy was used, and SEM with the SmartPLS 3.0 tool was used for data analysis. The Patimban Marine Industry in Subang Regency served as the study's site and its 97 respondents served as the research sample. The study's conclusions indicate that dedication, organizational culture, and ethical leadership all significantly improve organizational performance. Additionally, it showed to be positively significant between organizational cultural commitment and the impact of organizational culture on organizational performance as a mediating variable through commitment. However, ethical leadership has little of an effect on commitment, and it has much less of an effect on organizational performance when it acts as a facilitator of commitment. Keywords: Performance Organization; Leadership Ethics; Culture Organization; Commitment